Proposals for Green ICT campusthrough M-learning in Malaysian higher education institutions - Alla K.R.; Chen S.D. (Medwell Journals, 2023)
Mobile computing is under rapid development process and reached a stage where it is all set to replace the traditional computing of so called "work station" based operation. Malaysian Higher Education Institutions are aspiring to achieve Green ICT Campus as a commitment and responsibility for the Society and the Environment. This paper is about studying the current practices in Malaysian Higher Education Institutions and proposing various scenarios in making the campus as a Green ICT Campus through Mobile-Learning. Medwell Journals, 2016.